Traços consonantais identificadores do falar cuiabano na comunidade de São Gonçalo Beira Rio na contemporaneidade : conservação ou inovação? - Silva, Kenia Maria Corrêa da (2019)
ABSTRACT: The present work had as target to investigates consonant features of the speech of Cuiabá, in São Gonçalo Beira Rio community, located in Cuiabá, in Mato Grosso state, in contemporaneity. Interviews were made with locals to identify aspects of linguistic variation of such speech. It was investigated the most characteristic consonantal features found, such as: the variation between fricatives and affricates [∫] and [Ʒ] ~ [ʧ] and [ʤ], the variation between the allophones [s] ~ [∫] in initial syllables, the variation between the allophones [s] ~ [∫] in medial or final syllables, between the alveolar lateral and voiced alveolar [l] ~ [r] in consonantal groups - rhotacism, the variation between lateral, posterior semivowel and retroflex [l] ~ [w] ~ [ʵ] in position of medial or final syllables, the iodization [λ] ~ [j] and the exchange of [b] per [v] were addressed. Besides that, the history of the community of São Gonçalo Beira Rio was approached. This community has grown simultaneously with Cuiabá, and is characterized as a rural culture area. Afterwards, the occurences of these consonantal traits and the variations according to gender and age of the interwied speakers were described and analysed. It is possible to infer that the preservation of certain features are still found nowadays in the speech of Cuiabá might be inherited from the Galician Portuguese, therefore, being considered an archaic variant. It is also questioned if this speech is going through a proccess of maintenance or innovation.